2017
DOI: 10.1161/jaha.117.007519
|View full text |Cite
|
Sign up to set email alerts
|

Acute Coronary Syndrome: The Risk to Young Women

Abstract: BackgroundAlthough acute coronary syndrome (ACS) mainly occurs in patients >50 years, younger patients can be affected as well. We used an age cutoff of 45 years to investigate clinical characteristics and outcomes of “young” patients with ACS.Methods and ResultsBetween October 2010 and April 2016, 14 931 patients with ACS were enrolled in the ISACS‐TC (International Survey of Acute Coronary Syndromes in Transitional Countries) registry. Of these patients, 1182 (8%) were aged ≤45 years (mean age, 40.3 years; 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 44 publications
6
35
0
7
Order By: Relevance
“…52 Young women with ACS represent an extreme phenotype, given the protective effect of endogenous estrogen on the vascular endothelium and lipids. 53 The incidence of premature ACS among women is low 54 ; thus, we only recruited male patients with premature ACS. In recent years there is growing public awareness and increasing attention to young women with ACS.…”
Section: Limitationsmentioning
confidence: 99%
“…52 Young women with ACS represent an extreme phenotype, given the protective effect of endogenous estrogen on the vascular endothelium and lipids. 53 The incidence of premature ACS among women is low 54 ; thus, we only recruited male patients with premature ACS. In recent years there is growing public awareness and increasing attention to young women with ACS.…”
Section: Limitationsmentioning
confidence: 99%
“…Similar findings have been reported in previously conducted studies. 23,24,27 The results also revealed that AMI was more prevalent among male patients with 67.2%, while a smaller percentage of females (32.8%) had AMI. This finding is in good agreement with previous studies that have referred to male gender as a risk factor for ACS.…”
Section: Discussionmentioning
confidence: 79%
“…Patients were assigned into three groups according to their age: young group (<45 years), middle-age group (45-65 years), and old group (>65) based on similar studies on the same subject. [23][24][25]…”
Section: Inclusion/exclusion Criteriamentioning
confidence: 99%
“…В исследовании с участием 2873 женщин, которые находились под наблюдением в течение 24 лет, было показано, что смертность от ССЗ в постменопаузе в 2 раза выше, чем в пременопаузальном периоде [8].…”
Section: сердечно-сосудистые заболевания у женщинunclassified